Fusobacterium necrophorum and Actinomyces spp. masseter muscle abscessation in an adult alpaca. Issue 1 (22nd October 2022) - Poza, Marta Nieto; Connolly, Niall; Isgren, Cajsa; Talbot, Alison
Abstract: There are few documented cases of facial abscesses due to masseter abscess formation in South American camelids. Facial swellings in South American camelids have been reported and are frequently due to apical tooth root infections. Masseter abscess has been described in people. However, this lesion has not previously been described in South American camelids. This case report describes the clinical signs, diagnostic procedures and pathological findings in adult male Huacaya alpaca suffering from a masseter abscess caused by Fusobacterium necrophorum and Actinomyces spp. The mass was delimited by computed tomography and removed under general anaesthesia. The histopathology of the mass revealed severe focally extensive suppurative inflammation, which infiltrated and effaced the skeletal muscle. Bacterial cultures revealed that the abscess was caused by Fusobacterium necrophorum and Actinomyces spp. Once removed, the alpaca was started on antimicrobial therapy and did fully recover at the farm.